Institusionalisasi dan Disfungsi Sistem Hukum Perkawinan pada Praktik Kawin Lari - Mufti Ulil Amri (Indonesian Journal of Religion and Society, 2022)
This study aims to find a network of the phenomenon of the practice of elopement that occurs in the city of Padang. The aim of elopement in this discussion is more intended as an act of institutionalizing elopement in a negative sense, meaning that it violates the rules of religion, the state, and Minangkabau customary provisions which form the cultural locality of West Sumatra Province. The research question that is to be answer are how is the process of forming elopement networks?; what is the service pattern of the practice of elopement?; and what factors trigger the practice of elopement?. Research data obtained from observation, document study and interviews. This study tries to present data and qualitative analysis related to the problem of elopement in the city of Padang, which is the location where the research was conducted. From the research findings, it was concluded that even though it was prohibited by various norms, the existence of elopement services was recognized, the benefits were felt by elements of society, so that it continued to be accepted as a pattern of behavior and action as an alternative to marriage with various variant factors.